Sinamā lipi - Āriyadāsa, Eḍvin, 1922- (Văllampitiya : Divăsa Pracārakayō, 1985)
Transcript of lectures on motion-pictures and television broadcasting in Sri Lanka.
In Sinhalese.
Mode of access: Internet.
Keywords: Television broadcasting -- Sri Lanka; Motion pictures -- Sri Lanka